The Influence of Song Implementation on Early Childhood Language Skills: A Literature Review - Ginting, Eunike Laveda; Amini, Mukti; Chandrawati, Titi; Syarah, Erie Siti (Journal of English Language and Education, 2025)
This literature review explores the influence of song implementation on the development of language skills in early childhood. Songs are widely used as an engaging educational tool to introduce children to vocabulary, sentence structures, and concepts such as counting and environmental knowledge. This study aims to examine how the integration of songs in early learning environments supports language acquisition and communication development. Using a qualitative literature review approach, relevant studies were analyzed to identify patterns in the use of music for linguistic stimulation. The findings highlight that songs significantly enhance children's vocabulary, facilitate faster word recall, and improve long-term memory retention. Moreover, singing activities help reduce language delays by creating a relaxed, enjoyable learning atmosphere that encourages verbal expression. These results underscore the importance of incorporating music-based methods in early childhood education as a strategy to optimize language development.